FAKTOR PENYEBAB PERNIKAHAN BEDA AGAMA DI INDONESIA - Alfarisi, Usman; Fadil, Ahmad; Sadari, Sadari; Arrazy, Lazuardi Fadhlan (Hukum Islam, 2023)
This study aims to describe the factors causing interfaith marriages in Indonesia. The research method used is qualitative with a literature approach, where all data is obtained from relevant written materials. The research results show that the factors causing interfaith marriages in Indonesia include unharmonized regulations regarding interfaith marriages, differences in judges' perspectives when deciding cases, and the role of facilitators who provide a platform for couples wishing to marry across religions. This study emphasizes that interfaith marriages do not occur without cause but are supported by several factors that enable their occurrence. The implications of this study indicate the need for harmonizing regulations and increasing legal understanding related to interfaith marriages to reduce the incidence of such cases in the future. This is important to create harmony in law enforcement and provide legal certainty for the community.